2016
DOI: 10.1111/evo.13084
|View full text |Cite
|
Sign up to set email alerts
|

Genetic drift and mutational hazard in the evolution of salamander genomic gigantism

Abstract: GENETIC DRIFT AND MUTATIONAL HAZARD IN THE EVOLUTION OF SALAMANDER GENOMIC GIGANTISMSalamanders have the largest nuclear genome sizes among tetrapods and, with the exception of lungfishes, among vertebrates as a whole. Lynch and Conery (2003) have proposed the mutational hazard hypothesis to explain variation in genome size and complexity. Under this hypothesis, non-coding DNA imposes a selective cost by increasing the target for degenerative mutations, i.e. the mutational hazard. Expansion of non-coding DNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 83 publications
(206 reference statements)
0
24
0
Order By: Relevance
“…The large salamander genomes, and other giant genomes in plants and insects, have been attributed to a slow deletion rate of DNA (Bensasson, Petrov et al 2001, Sun, López Arriaza et al 2012, Kelly, Renny-Byfield et al 2015, suggesting that these genomes are genetically more stable compared to taxa with smaller genomes. In the case of salamanders, the slow loss of DNA has been associated with significantly lower mutation rates in these organisms compared to other vertebrates (Mohlhenrich and Mueller 2016). Other studies have shown a similar negative relationship between genome size and mutation rates (Dores, Sollars et al 1999, Herrick andSclavi 2014), but the exact nature of the relationship, if any, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 90%
“…The large salamander genomes, and other giant genomes in plants and insects, have been attributed to a slow deletion rate of DNA (Bensasson, Petrov et al 2001, Sun, López Arriaza et al 2012, Kelly, Renny-Byfield et al 2015, suggesting that these genomes are genetically more stable compared to taxa with smaller genomes. In the case of salamanders, the slow loss of DNA has been associated with significantly lower mutation rates in these organisms compared to other vertebrates (Mohlhenrich and Mueller 2016). Other studies have shown a similar negative relationship between genome size and mutation rates (Dores, Sollars et al 1999, Herrick andSclavi 2014), but the exact nature of the relationship, if any, remains to be elucidated.…”
Section: Introductionmentioning
confidence: 90%
“…Insights into how their genomes are structured and function therefore remain limited [e.g. 12, [13][14][15].…”
Section: Main Text: the Extent Of Genome Size Diversity Across Eukarymentioning
confidence: 99%
“…Certainly, recent studies (e.g. genome skimming approaches using high throughput sequencing technologies) of giant genomes in animals and plants suggest that the composition, regulation and evolution of their genomes may be following different trajectories compared with species possessing smaller genomes [12][13][14][15]27].…”
Section: What Mechanisms Prevent Genomes From Uncontrolled Expansion?mentioning
confidence: 99%
“…Therefore, there was still some controversy about the mutational-hazard hypothesis (Whitney and Garland 2010;Cohen et al, 2012). For example, Mohlhenrich analyzed the non-coding genes of salamanders and frogs, he concluded that the mutational hazard did not play a mainly role in the genomic gigantism of salamanders (Mohlhenrich and Mueller, 2016). But there are still some studies that support the mutational-hazard hypothesis.…”
Section: Introductionmentioning
confidence: 99%